Endoscopic Management of Developmental Anomalies of the Skull Base - Wilson, Meghan; Snyderman, Carl (Journal of Neurological Surgery Part B: Skull Base, 2018)
Developmental anomalies of the skull base may present in childhood or as an adult. The most common pathologies include dermoid, encephalocele, and glioma. Encephaloceles may present as part of a syndrome. Other entities include infantile hemangiomas and teratoma. Endoscopic techniques provide a less invasive and morbid option for treatment. Proper evaluation and treatment is necessary to prevent complications such as meningitis.
Keywords: dermoid encephalocele; developmental; glioma; teratoma